Cyberspace and its relationship to psychosocial compatibility (Snapchat as a model): A field study on a sample of middle school students in some schools in Jeddah in Saudi Arabia - Alobedi, Nada Abdullah; Saeed, Sahar (Al-Adab Journal, 2021)
The study aims to investigate the extent of the relationship between cyberspace and psychosocial compatibility among middle school students in some schools in Jeddah from a social perspective. The study used the descriptive-analytical method applied to a random sample of middle school students in some schools in the city of Jeddah, sample (211 students), and adopted the study on the psychological dimensions of social consensus standards for data collection, the results showed a correlation between cyberspace (Snapchat) and compatibility (social-emotional - self with the sample of students in the intermediate stage, (Snapchat The social-emotional-self-consensus of the sample members of middle school students, and the group is of respondents of middle school students who use the Snapchat website daily (always) are more in agreement with each of the three measures (social compatibility, emotional compatibility, and self-compatibility) than those who use Snapchat owns a daily basis who (rarely, sometimes), and the group of respondents of middle school students who average use daily.